Development and validation of a portable TDLAS system for gas chromatography–level quantification of methane emissions from rice - Sujeevan Rajendran; Wonbok Lee; Sun Hwa Lee; Dongjin Shin; Da Hee Jung; Yu Mi Kang; Seok-in Yun; Byoung Il Je; Chul Min Kim; Young Hun Song (Plant Biotechnology Reports, 2025)
Rice cultivation is a significant source of agricultural methane (CH₄), yet routine quantification still relies heavily on gas chromatography (GC), which limits throughput and field deployment. Here, we evaluated a portable tunable-diode-laser absorption spectroscopy (TDLAS) detector (PMD) as an alternative to GC for measuring CH₄ released from pot-grown rice plants under field conditions. Weekly closed-chamber samples from five cultivars were analyzed in parallel by GC (FID/MS) and the PMD. Standard gas tests showed an excellent linear relationship for the PMD (R 2 = 0.9995), indicating a near-ideal response. Across field samples, GC and PMD were strongly associated (R 2 = 0.9943). Bland–Altman analysis revealed a mean bias (GC − PMD) of 8.55 with 95% limits of agreement − 9.16 to 26.26, and Lin’s concordance correlation coefficient was 0.991, evidencing near-perfect agreement despite a slight systematic offset. A simple calibration with a linear regression eliminated the bias and narrowed the limits of agreement, while preserving the high correlation. Residual analyses suggested a modest influence of CO₂ (but not N₂O) on between-method differences. Taken together, the PMD provides rapid, robust, and labor-efficient CH₄ measurements that closely match GC when a fixed calibration is applied, enabling high-throughput phenotyping of rice genotypes and management practices in both laboratory and field settings. This calibrated, portable approach lowers barriers to large-scale screening for low-emission rice, supporting climate-smart crop improvement.

Spatiotemporal distributions of total and methylmercury in bivalves from coastal zones of South Korea - Haein Yu; Geonwoo Park; Chul-In Sun; Yong Hwa Oh; Yong-Woo Lee (Marine Pollution Bulletin, 2025)

Biogeochemical cycling of sedimentary organic carbon and benthic nutrient fluxes in the semi-enclosed Jinhae Bay, Korea: insights into benthic-pelagic coupling - Sung-Uk An; Kyung-Tae Kim; Sung-Han Kim; Ju-Wook Baek; Hyun-Jeong Jeong; Chul-In Sun; Jin Young Choi; Sokjin Hong; Dae In Lee; Jae Seong Lee (Frontiers in Marine Science, 2025)
The mineralization of organic matter at the sediment plays a crucial role in ecosystem functioning by facilitating the biogeochemical cycling of carbon and nutrients. This process not only supports nutrient availability for primary production but also regulates the long-term storage of carbon within sediments. To understand the biogeochemical processes associated with organic matter mineralization and nutrient regeneration, we estimated total and diffusive sediment oxygen uptake rates, benthic nutrient fluxes, and organic carbon (OC) budgets at four sites in the semi-enclosed Jinhae Bay (JB). The total oxygen uptake (TOU) rates ranged from 38.4 to 49.6 mmol O 2 m –2 d –1 , and diffusive oxygen uptake (DOU) rates ranged from 12.3 ± 1.8 to 15.1 ± 1.4 mmol O 2 m –2 d –1 . The average ratio of TOU : DOU ranged from 3.12 to 3.28 over JB, which suggests significant benthic faunal activities in JB sediments. The vertical flux of organic carbon ranged from 45.5 ± 7.0 to 93.0 ± 25.3 mmol C m -2 d –1 , and mainly consisted of biodeposits associated with aquaculture activities. The burial flux into the sediment ranged from 3.96 ± 1.00 to 7.17 ± 1.64 mmol C m –2 d –1 , and burial efficiencies were 4.25 to 15.8%, which indicated that deposited organic carbon was either mineralized in surface sediment before burial or laterally transferred by resuspension. The benthic nutrient fluxes at four sites ranged from 1.50 to 2.07 mmol m –2 d –1 for nitrogen, from 0.02 to 0.05 mmol m –2 d –1 for phosphate, and from 6.72 to 9.11 mmol m –2 d –1 for silicate. The benthic nitrogen and phosphate fluxes accounted for 82.1 to 149% and 23.1 to 57.6%, respectively, of the required levels for primary production in the water column. Our results suggest that OC oxidation in the JB sediment may significantly contribute to the biogeochemical OC cycles and tight benthic–pelagic coupling associated with nutrient regeneration.

Pollen-mediated flow of bar gene in transgenic herbicide-resistant turf grass Zoysia japonica - Hong-Gyu Kang; Ok-Chul Chung; Tae-Woong Bae; Hyeon-Jin Sun; In-Ja Song; Kee Woong Park; Pyung-Ok Lim; Jaechun Lee; Yong-Eok Lee; Pill-Soon Song; Hyo-Yeon Lee (Plant Biotechnology Reports, 2021)

Complete genome sequence of a novel reassortant H3N3 avian influenza virus - Tran Bac Le; Hey Kwon Kim; Hai Yen Le; Min-Chul Jeong; In-Kyu Kim; Dae Gwin Jeong; Sun-Woo Yoon (Archives of Virology, 2019)

Spatial distribution and pollution assessment of metals in intertidal sediments, Korea - Dong-Woon Hwang; Pyoung-Joong Kim; Seong-Gil Kim; Chul-In Sun; Byoung-Seol Koh; Sang-Ok Ryu; Tae-Hoon Kim (Environmental Science and Pollution Research, 2019)

Sound wave affects the expression of ethylene biosynthesis-related genes through control of transcription factors RIN and HB-1 - Joo Yeol Kim; Hye Ryun Ahn; Sun Tae Kim; Cheol Woo Min; Soo In Lee; Jin A. Kim; Soo-Chul Park; Mi-Jeong Jeong (Plant Biotechnology Reports, 2016)

Production of transgenic spermatozoa by lentiviral transduction and transplantation of porcine spermatogonial stem cells - Byung-Gak Kim; Yong-Hee Kim; Yong-An Lee; Bang-Jin Kim; Ki-Jung Kim; Sang-Eun Jung; Hak-Jae Chung; Seongsoo Hwang; Sun-Ho Choi; Myung Jick Kim; Dong-Hoon Kim; In Cheul Kim; et al. (Tissue Engineering and Regenerative Medicine, 2014)

The prevalence of BRCA mutations among familial breast cancer patients in Korea: results of the Korean Hereditary Breast Cancer study - Sang-Ah Han; Sung-Won Kim; Eunyoung Kang; Sue K. Park; Sei-Hyun Ahn; Min Hyuk Lee; Seok-Jin Nam; Wonshik Han; Young Tae Bae; Hyun-Ah Kim; Young Up Cho; Myung Chul Chang; et al. (Familial Cancer, 2013)

Occurrence of bacterial rot of onion caused by Bacillus amyloliquefaciens in Korea - Sun-Kyoung Hwang; Chang-Gi Back; Nang Kyu Kyu Win; Myung Kyum Kim; Hee-Dae Kim; In-Kyu Kang; Sang-Chul Lee; Hee-Young Jung (Journal of General Plant Pathology, 2012)

Overexpression of the pepper antimicrobial protein CaAMP1 gene regulates the oxidative stress- and disease-related proteome in Arabidopsis - Sung Chul Lee; In Sun Hwang; Byung Kook Hwang (Planta, 2011)

The pepper oxidoreductase CaOXR1 interacts with the transcription factor CaRAV1 and is required for salt and osmotic stress tolerance - Sung Chul Lee; Du Seok Choi; In Sun Hwang; Byung Kook Hwang (Plant Molecular Biology, 2010)

Differential expression of two glutamate transporters, GLAST and GLT-1, in an experimental rat model of glaucoma - Chan Kee Park; Jiook Cha; Soo Chul Park; Phil Young Lee; Jie Hyun Kim; Hwa Sun Kim; Shin Ae Kim; In-Beom Kim; Myung-Hoon Chun (Experimental Brain Research, 2009)

Pepper pectin methylesterase inhibitor protein CaPMEI1 is required for antifungal activity, basal disease resistance and abiotic stress tolerance - Soo Hyun An; Kee Hoon Sohn; Hyong Woo Choi; In Sun Hwang; Sung Chul Lee; Byung Kook Hwang (Planta, 2008)

Characterization of copper, zinc superoxide dismutase from a cartilaginous shark species, Scyliorhinus torazame (Carcharhiniformes) - Yoon Kwon Nam; Young Sun Cho; Keun-Yong Kim; In Chul Bang; Ki Hong Kim; Sung Koo Kim; Dong Soo Kim (Fish Physiology and Biochemistry, 2006)

Functional roles of the pepper pathogen-induced bZIP transcription factor, CAbZIP1, in enhanced resistance to pathogen infection and environmental stresses - Sung Chul Lee; Hyong Woo Choi; In Sun Hwang; Du Seok Choi; Byung Kook Hwang (Planta, 2006)

Production of biologically active human granulocyte colony stimulating factor in the milk of transgenic goat - Jung Ho Ko; Chul-Sang Lee; Kui Hyun Kim; Myung-Geol Pang; Ja Shin Koo; Nanzhu Fang; Deog-Bon Koo; Keon Bong Oh; Woo-Sik Youn; Guo Dong Zheng; Jung Sun Park; Sun Jung Kim; et al. (Transgenic Research, 2000)